Evaluating democratic governance: A bottom up approach to European Union enlargement - Richard Rose (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Although analyses of democracy and governance may be complementary rather than in conflict, they are not identical. This article compares the EU criteria for evaluating applicants for membership with those of democracy indexes. It uses data from the 13- country New Europe Barometer surveys of public opinion to provide a bottom up evaluation of democratic governance in Bulgaria, Romania, Croatia and Ukraine. The results are compared, point by point, with the minimum evaluation of governance in the eight Central and East European countries admitted to the EU in 2004. Factor analysis confirms statistically that these measures are multi-dimensional; in other words, democratic governance cannot be reduced to a one-dimensional index of democracy. The conclusion emphasizes the advantages of thinking in terms of democratic governance not only for diagnosing and prescribing governmental reforms but also for academics monitoring democratization as a process that may only be partially successful.
Keywords: 300; Demokratie; Governance-Ansatz; Bewertung; EU-Erweiterung; EU-Staaten